Exposures to molds in school classrooms of children with asthma. Issue 7 (8th October 2013) - Baxi, Sachin N.; Muilenberg, Michael L.; Rogers, Christine A.; Sheehan, William J.; Gaffin, Jonathan; Permaul, Perdita; Kopel, Lianne S.; Lai, Peggy S.; Lane, Jeffrey P.; Bailey, Ann; Petty, Carter R.; Fu, Chunxia; et al.
Abstract Background Students spend a large portion of their day in classrooms which may be a source of mold exposure. We examined the diversity and concentrations of molds in inner‐city schools and described differences between classrooms within the same school. Methods Classroom airborne mold spores, collected over a 2 day period, were measured twice during the school year by direct microscopy. Results There were 180 classroom air samples collected from 12 schools. Mold was present in 100% of classrooms. Classrooms within the same school had differing mold levels and mold diversity scores. The total mold per classroom was 176.6 ± 4.2 spores/m3 (geometric mean ± standard deviation) and ranged from 11.2 to 16, 288.5 spores/m3. Mold diversity scores for classroom samples ranged from 1 to 19 (7.7 ± 3.5). The classroom accounted for the majority of variance (62%) in the total mold count, and for the majority of variance (56%) in the mold diversity score versus the school. The species with the highest concentrations and found most commonly included Cladosporium (29.3 ± 4.2 spores/m3), Penicillium/Aspergillus (15.0 ± 5.4 spores/m3), smut spores (12.6 ± 4.0 spores/m3), and basidiospores (6.6 ± 7.1 spores/m3). Conclusions Our study found that the school is a source of mold exposure, but particularly the classroom microenvironment varies in quantity of spores and species among classrooms within the same school. We also verified that visible mold may be a predictor for higher mold spore counts. Further studies are needed to determine the clinical significance of mold exposure relative to asthma morbidity in sensitized and non‐sensitized asthmatic children.